Determination of stress in fish community obtained from shrimp trawl fishing in Northern Gulf of California - Herrera-Valdivia, Eloísa (2015)
Bottom trawling has been considered a fishing activity that affects and modifies habitats, because of its impacts in species composition and abundance, and the alteration in the structure and function of the ecosystem, that generates biodiversity loss. The Northern part of the Gulf of California has been considered a mega diverse zone with high endemism, and it is of growing interest by the international scientific community. In order to assess its potential changes in the fish community components of shrimp by-catch (FAC) in this area, a total of 119 trawls from 13 fishing boats were analyzed in Puerto Peñasco, based on 14 commercial fishing trips made within 9-90 m depth from 2010-2011. A random sample of 20 kg was obtained from each trawl, and was analyzed in the laboratory for species composition. In addition to the Index of Biological Value (IVB), Shannon diversity (H'), and Pielou evenness (J'), comparative abundance-biomass curves (ABC) were also estimated. Eucinostomus dowii showed the highest IVB = 480.25; Porichthys analis showed greater relative abundance; and Pomadasys panamensis showed greater frequency of occurrence. The mean monthly values in diversity H’ = 3.05 (2.72 > H’ < 3.25) and J’ = 0.71 (0.66 < J’ >0.81) showed a tendency to decrease as the fishing season progressed. The comparative abundance-biomass curves (ABC), and the value of statistical W showed moderate stress levels in March (W = -0.022) and September (W = -0.02) 2010, and January 2011 (W = -0.042). In conclusion, the Northern Gulf of California showed a well-structured community with a degree of moderate fishing stress.